Formulation of value added chicken meatball with different level of wheat flour (SAARC Journal of Agriculture, 2018)
The present study was undertaken to evaluate the effect of different levels of wheat flour on the quality characteristics of chicken meatball. Wheat flour which acts as a binding agent of meatball except for control group T1. The meatballs were formulated having 0%, 5%, 10% and 15% wheat flour. The sensory (colour, flavour, texture, juiciness, tenderness, overall acceptability), physicochemical (proximate analysis, pH, cooking loss), biochemical (TBARs, POV, FFA) were analyzed. Treatments were analyzed in a 4×3 factorial experiment in CRD replicated three times per cell. Wheat flour inclusion in meatballs increased cooking yield by reducing weight loss from 27.06 to 26.49%. Among four treatments most preferable colour, odour, tenderness, juiciness was observed significantly (p